2020
DOI: 10.1111/cts.12832
|View full text |Cite
|
Sign up to set email alerts
|

A Pooled Analysis of Three Randomized Phase I/IIa Clinical Trials Confirms Absence of a Clinically Relevant Effect on the QTc Interval by Umibecestat

Abstract: Umibecestat, an orally active β-secretase inhibitor, reduces the production of amyloid beta-peptide that accumulates in the brain of patients with Alzheimer's disease. The echocardiogram effects of umibecestat, on QTcF (Fridericia-corrected QT), on PR and QRS and heart rate (HR), were estimated by concentration-effect modeling. Three phase I/II studies with durations up to 3 months, with 372 healthy subjects over a wide age range, including both sexes and 2 ethnicities, were pooled, providing a large data set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, the manual patch clamp assay showed, in contrast, an IC 50 > 10 μM. No QTc prolongation was detected in animal safety studies nor in human phase I and IIa studies of compound 15 . We attribute the favorable cardiosafety profile of 15 to the low free plasma exposure at active doses.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the manual patch clamp assay showed, in contrast, an IC 50 > 10 μM. No QTc prolongation was detected in animal safety studies nor in human phase I and IIa studies of compound 15 . We attribute the favorable cardiosafety profile of 15 to the low free plasma exposure at active doses.…”
Section: Resultsmentioning
confidence: 76%
“…No QTc prolongation was detected in animal safety studies nor in human phase I and IIa studies of compound 15. 36 We attribute the favorable cardiosafety profile of 15 to the low free plasma exposure at active doses. This compound, which offered the best overall profile, in terms of BACE1/BACE2 selectivity, pharmacodynamic, and pharmacokinetic properties, was further profiled for transition to clinical studies in humans.…”
Section: Resultsmentioning
confidence: 98%
“…However, APP cleavage via β and γ-secretase results in a sAPPβ fragment and Aβ peptide, the primary component of amyloid plaques in AD [26,27]. Several human clinical trials for AD have focused on inhibition of β and γ-secretase to decrease Aβ production [28][29][30][31][32][33][34]. Although these trials showed a decrease in plasma and CSF Aβ levels, they have failed when it comes to establishing safety and efficacy.…”
Section: Aβ Pathologymentioning
confidence: 99%
“…Although these trials showed a decrease in plasma and CSF Aβ levels, they have failed when it comes to establishing safety and efficacy. These trials have been discontinued based on increased incidence of skin cancer and worsening cognitive scores [29][30][31][32][33][34].…”
Section: Aβ Pathologymentioning
confidence: 99%
See 1 more Smart Citation